“Por ser de lá...”: experiências de escolarização e trabalho de jovens monitoras/es egressas/os de Escolas Família Agrícola de Minas Gerais - Jeane Soares da Paixão (2024)
This research’s main objective is to understand the schooling and work experiences of young people who have graduated from EFAs - Escolas Família Agrícola (Agricultural Family Schools in free translation) that return to these institutions to work as tutors. The EFAs are institutions created as associations to meet the educational needs of the rural families who have historically had this right denied to their children. The theoretical and methodological framework presents a dialog with researchers from Educação do Campo (Rural Education, in free translation), EFAs and Juventudes do campo (Rural Youth, in free translation). The study included a quantitative (questionnaire) and a qualitative (semi-structured interviews) phase. The questionnaire was developed and applied in collaboration with the Associação Mineira das Escolas Família Agrícola (AMEFA - Minas Gerais Association of Agricultural Family Schools, in free translation), and tutors from the 22 EFAs located in Minas Gerais, covering 198 respondents. It allowed us to draw up a profile of the tutors and identify potential participants for the second phase of the study. Hence, the interviews were conducted with seven tutor through the Microsoft Teams platform. The results of this research show that there is a substantial number of young graduates working as tutors in the EFAs surveyed. As for schooling, most of these young people had most of their education in schools located in the city, often with a curriculum far removed from the reality of the rural areas, and having to face numerous pre-judgements. The research showed that the return of these young adults as tutors has been encouraged by the schools as a way of ensuring that these establishments have professionals capable of contributing effectively with their educational purpose. Furthermore, individually, this choice has been motivated by the activism in rural movements, for the identification with the EFAs training project, for the opportunity of entering the workforce, becoming an alternative that is described by some as “a dream”. Finally, the rotation of tutors is a challenge to be overcome by these schools, which requires public policies to support these entities in solving this issue.